Pengaruh Prenatal Yoga terhadap Penurunan Nyeri Punggung pada Ibu Hamil Trimester III di PMB Usmalanah Bandar Lampung Tahun 2024 - Halima Tusakdiyah; Astriana Astriana; Febriyantina Parina; Anissa Ermasari (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Based on data in the United States, Europe and several regions of Africa, back pain affects 30% to 78% of pregnant women.Pre-survey results conducted at PMB UsmalanahdatIn the April 2024 period, the number of TM III pregnant women was 37 people. Of the 10 third trimester pregnant women through interviews, 7 (70%) had back pain and 3 (30%) had no back pain.This type of quantitative research with an experimental design.The population of third trimester pregnant women who complained of back pain at PMB Usmalanah was 34 respondents. The sample size in this study was the entire population. Independent variable: prenatal yoga and dependent variable: back pain. The sampling technique used ispurposive sampling technique.Data were collected using the NRS pain scale observation sheet. Data were analyzed univariately and bivariately, the test used was the dependent T-test.The results of the study showed: the average back pain score before prenatal yoga was 4.76 (in the moderate pain category), the average back pain score after prenatal yoga was 2.55 (in the mild pain category). Based on the results of the Wilcoxon Signed Test calculation, the z value obtained is – 5.143 with a p value of 0.000. The conclusion of this research is that there is an effect of Prenatal Yoga on reducing back pain in TM III pregnant women at PMB Usmalanah Bandar Lampung. Advice for pregnant womenIt is hoped that non-pharmacological therapy will be preferred to reduce back pain. Because not all medicines can be consumed by pregnant women.